2019
DOI: 10.1111/1747-0080.12524
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intervention strategies for ethnic Chinese women with gestational diabetes mellitus: A systematic review and meta‐analysis

Abstract: AimEthnic Chinese women are one of the populations at high risk of gestational diabetes mellitus (GDM) internationally. This systematic review aimed to determine which dietary intervention strategies were found to be effective in improving glycaemic control and pregnancy outcomes among ethnic Chinese women with GDM.MethodsThe review protocol was registered with PROSPERO (CRD42016043585). Eight English and four Chinese language databases were searched for randomised controlled trials and cohort studies of dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…The most current Cochrane analysis [63] did not show significant maternal and/or infant benefits; in contrast, Yamamoto et al [64] focused their primary analysis on maternal glycemic outcomes and concluded that interventions that improved maternal glycemic control would improve infant birthweight outcomes. In agreement was another meta-analysis by Wan et al [65] who focused their meta-analysis on dietary intervention strategies to include all Chinese-language studies. Their conclusion was that CHO-modified diets were associated with improved glycemic control and infant birth outcomes in ethnic Chinese women with GDM.…”
Section: Role Of Dietary Carbohydrates In Gdmmentioning
confidence: 71%
“…The most current Cochrane analysis [63] did not show significant maternal and/or infant benefits; in contrast, Yamamoto et al [64] focused their primary analysis on maternal glycemic outcomes and concluded that interventions that improved maternal glycemic control would improve infant birthweight outcomes. In agreement was another meta-analysis by Wan et al [65] who focused their meta-analysis on dietary intervention strategies to include all Chinese-language studies. Their conclusion was that CHO-modified diets were associated with improved glycemic control and infant birth outcomes in ethnic Chinese women with GDM.…”
Section: Role Of Dietary Carbohydrates In Gdmmentioning
confidence: 71%
“…In particular, consuming a diet based on low-glycemic index (GI) foods results in better glycemic control than following conventional healthy dietary recommendations [ 8 , 9 ]. A meta-analysis conducted in 2019 that included 29 studies compared different dietary strategies for glycemic control among Chinese women with GDM [ 10 ]. Six of them compared a low-GI diet with standard dietary interventions and found that low-GI diets were associated with improved glycemic control.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary intervention strategies for ethnic Chinese women with gestational diabetes mellitus is explored in a systematic review and meta-analysis of 29 studies (n = 3944). 30 Low glycaemic index, low glycaemic load and fibre-enriched diets were associated with improved glycaemic control and pregnancy outcomes. Further research directly comparing these intervention strategies is required.…”
mentioning
confidence: 97%
“…From 10 randomised controlled trials of 1530 participants, dietetic counselling was effective for lowering tryglycerides and at least as effective as usual or minimal care for improving cholesterol. Dietary intervention strategies for ethnic Chinese women with gestational diabetes mellitus is explored in a systematic review and meta‐analysis of 29 studies (n = 3944) . Low glycaemic index, low glycaemic load and fibre‐enriched diets were associated with improved glycaemic control and pregnancy outcomes.…”
mentioning
confidence: 99%